Dormancy and Seed Germination in Thespesia lampas Dalz. & Cibs : a Potential Agro Forestry and Medicinal Species - Chitra Devi, L.; Pandey, Sushil; Kak, Anjali; Gupta, Veena (Indian Forester, 2007)
Thespesia lampas Dalz. & Cibs is a wild medicinal shrub of India. The seeds of this species remain fresh and hard even after 60 days of viability test, suggesting the presence of seed coat dormancy/hard seededness. The tetrazolium test confirmed 100 % viability. This type of dormancy creates problems for the seed analysts while performing laboratory germination test and also during seed regeneration for germplasm managers and plant breeders. To determine the most suitable means of overcoming seed coat dormancy in T. lampas, seeds were exposed to various pre-treatments such as scarification in sand paper, hot water and sulphuric acid. Treated seeds were evaluated for their quality parameters to assess the impact of given treatments. The results revealed that soaking seeds in hot water at 75Â°C for 10 minutes was found to be most suitable treatment of enhancing germination. The present study provides means to overcome physical dormancy and enhance seed germination of this important medicinal species.